Diabetes Melitus sebagai Komorbiditas Utama terhadap Mortalitas Pasien COVID-19 - Zahra Salsabila; Yani Triyani; Sadiah Achmad (Jurnal Riset Kedokteran, 2023)
Abstract. The purpose of this study was to analyze the relationship between comorbidities and mortality in COVID-19 patients. This study uses analytic methods with a cross-sectional research design. Data were obtained from the medical records of inpatients with confirmed COVID-19 at Al-Islam Hospital Bandung for the 2021 period. The statistical test used a univariate data test by looking at the characteristics of COVID-19 patients based on age, sex, and length of stay and using the Chi test -Square to analyze whether there is a relationship between the independent and dependent variables. The number of respondents in this study was 2,047 people, with the most age being ≥60 years (39.5%), male sex (51.3%), with the highest comorbidity diabetes mellitus (41.9%), followed by hypertension (35.7%) and renal disease (12.4%) which have CFR values of 10.1%, 5.9%, and 5.2% respectively. Patients with comorbid diseases have a decreased immune response and the location of ACE-2 receptors is found not only in the respiratory tract but also in other organs such as the pancreas and kidneys. The conclusion shows that there is a relationship between comorbidities and mortality of COVID-19 patients at Al-Islam Hospital Bandung in 2021 with a p-value <0.001 (p <0.05). Abstrak. Tujuan penelitian ini adalah menganalisis hubungan komorbiditas dengan mortalitas pasien COVID-19. Penelitian ini menggunakan metode analitik dengan rancangan penelitian cross sectional. Data diperoleh dari rekam medis pasien rawat inap yang terkonfirmasi COVID-19 di Rumah Sakit Al-Islam Bandung Periode 2021. Uji Statistik menggunakan uji data univariat dengan melihat karakteristik pasien COVID-19 berdasarkan usia, jenis kelamin, dan lama rawat inap serta menggunakan uji Chi-Square untuk menganalisis ada tidaknya hubungan antara variable bebas dan terikat. Jumlah responden pada penelitian ini sebanyak 2.047 orang, dengan usia yang paling banyak  ≥60 tahun (39,5%), jenis kelamin laki-laki (51,3%), dengan komorbiditas tertinggi diabetes melitus (41,9%), disusul dengan hipertensi (35,7%) dan renal disease (12,4%) yang memiliki nilai CFR berturut-turut 10,1%, 5,9%, dan 5,2%. Pasien dengan penyakit komorbid berada dalam penurunan respon imun serta lokasi reseptor ACE-2 yang ditemukan tidak hanya di saluran respirasi, tetapi juga didapatkan di organ lain seperti pankreas dan ginjal. Kesimpulan menunjukkan terdapat hubungan komorbiditas dengan mortalitas pasien COVID-19 di RS Al-Islam Bandung tahun 2021 dengan nilai p <0.001 (p<0.05).